Effectiveness of sigmoidoscopy or colonoscopy screening on colorectal cancer incidence and mortality: a systematic review and meta-analysis of randomized controlled trial - Han, Chunyang; Wu, Fan; Xu, Jian (Frontiers in Oncology, 2024)
Objectives: We conducted a comprehensive analysis to compare colonoscopy and sigmoidoscopy with standard care or fecal immunochemistry regarding colorectal cancer incidence and mortality risk. Methods: Until August 2023, literature from PubMed, Embase, Web of Science, and Cochrane was systematically reviewed. We examined the impact of colonoscopy or sigmoidoscopy versus standard care on colorectal cancer outcomes, including incidence, cancer-specific mortality, and overall mortality. Results: Among 4,265 screened articles, data from seven randomized controlled trials (involving 663,319 participants) were analyzed. The intervention group (colonoscopy or sigmoidoscopy) consisted of 258,938 participants, while the control group received standard care or fecal immunochemical testing, totaling 404,381 participants, with both groups having average colorectal cancer risk, without confounders. Pooled analyses indicated a 20% reduction in colorectal cancer incidence (RR: 0.80, 95% CI: 0.77-0.83) and a 26% decrease in colorectal cancer mortality (RR: 0.74, 95% CI: 0.69-0.80) in the intervention group compared to standard care. All-cause mortality remained unchanged (RR: 1.03, 95% CI: 0.99-1.07). Subgroup analysis favored sigmoidoscopy in reducing colorectal cancer morbidity and mortality. Conclusion: This meta-analysis of randomized controlled trials underscores the effectiveness of colonoscopy and, notably, sigmoidoscopy in reducing colorectal cancer incidence and mortality among average-risk populations. In comparison to fecal immunochemical testing, both colonoscopy and sigmoidoscopy did not significantly impact colorectal cancer incidence and mortality in this population.